All-Optical Parametric-Assisted Oversampling and Decimation for Signal Denoising Amplification - Fernández, Manuel Pablo (2023)
Decimation is a common process in digital signal processing that involves reducing the sampling rate of an oversampled signal by linearly combining consecutive samples. Among other applications, this process represents a simple means to mitigate noise content in the digital signal. In this work, a novel optical signal processing concept inspired by these operations is proposed, which is called Parametric-assisted Oversampling and Decimation (POD). By using a simple all-fiber setup, the POD processor first realizes an ultra-fast parametric oversampling of the incoming temporal signal (at >100 Gigasamples per second), a process that is followed by a decimation that reduces the sampling rate by any user-defined factor in a lossless manner. In this way, the POD delivers an amplified sampled copy of the optical signal, where the peak-to-peak gain results from the combination of parametric amplification and a “passive” amplification equal to the decimation factor. In this report, joint parametric and passive amplification by a factor ≈50 on GHz-bandwidth signals is demonstrated. Furthermore, it is shown that the decimation process can effectively mitigate effects of narrowband noise, outperforming traditional optical and digital filtering techniques. By experimentally achieving ultra-high decimation factors (>750), narrowband (MHz-bandwidth) optical waveformsthat are lost in a much stronger noise background are recovered.